(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Coccidiosis is one of the major economically important diseases of poultry worldwide. In Bangladesh, coccidiosis is one of the major threats for commercial poultry industry as well. Successful control of chicken coccidiosis in Bangladesh mainly depends on the application of anticoccidial drugs (ACD) in ration of chickens during grow-out. There are some reports on the occurrence of coccidiosis in broiler chickens in Bangladesh, but information on track changes in Eimeria oocysts levels and species composition in commercial broiler farms over time during ACD program is very scarce. The purpose of this study was to investigate the oocyst concentrations and species composition of Eimeria in litter from commercial broiler houses during ACD control programs. Litter samples were collected from a total of 22 different broiler farms during at least one complete grow-out cycle. Samples were collected at 0, 1, 2, 3 and 4 week (wk) of grow-out of the ACD cycle. We succeeded for isolation of Eimeria oocysts from the litter samples of 14 broiler farms, and coccidian species were identified by previously described morphological characteristics using standard shape index method under microscopy. Eimeria oocyst concentration in litter was found to be reached in peak levels at 3–4 wk of grow-out cycle. However, sudden peak level of oocysts of Eimeria spp in 8 farms indicated to develop some drug resistance. E. tenella, E. necatrix and E. acervulina were generally found to be to present in the most of the samples. Findings of this study will be helpful to develop an appropriate control strategy against chicken coccidiosis in Bangladesh. J Bangladesh Agril Univ 18(4): 1001–1006, 2020 https://doi.org/10.5455/JBAU.20468